CEO Political Connection, Shareholding and Financial Distress of Deposit Money Banks in Nigeria - Agbo, Emmanuel; Egbunike, Chinedu (International Journal of Financial, Accounting, and Management, 2024)
Purpose: Prior studies conducted to investigate the issues of CEO political connection and shareholding on financial distress remain inconclusive. It is based on the above, that this study is set out to examine the effect of CEO political connection and shareholding on the financial distress of DMBs. Methodology/approach: This study adopted an ex post facto research design based on the nature and the problem of the research. The study utilized annual financial data from quoted DMBs from 2012 to 2021. The data were subjected to diagnostic tests and the Hausman test selected the use of REM over the FEM for testing the hypotheses. Results/findings: The main results show that CEOP (?=0.275582; p=0.7029) had a positive non-significant effect on financial distress; CEOS (?=-0.201171; p=0.0039) had a negative significant effect on financial distress. Limitations: The study does not include other control variables such as firm size and firm leverage which can also affect financial distress. Contribution: This research contributes first, from the focus on developing country settings is important from a theoretical and empirical standpoint because the findings help us comprehend how political connection and shareholding status of CEOs determine the distress score of the DMBs in the absence of a supportive corporate and legal framework. Novelty: This study from the context of a developing nation with weak institutional governance, examines how CEO political connection and shareholding explain the financial distress score of the DMBs which prior studies have weakly examined.